Aristotle’s Solution for Parmenides’ Inconclusive Argument in Physics I.3 - Angioni, Lucas (Peitho. Examina Antiqua, 2021)
I discuss the argument which Aristotle ascribes to Parmenides at Physics 186a23–32. I examine (i) the reasons why Aristotle considers it to be eristic and inconclusive and (ii) the solution (lusis) that he proposes against it.